MODERN WRITER AND ARTIFICIAL INTELLIGENCE - CO-AUTHOR, ASSISTANT, OR ADVERSARY? - Mirtskhulava, L (SWorld-Ger Conference proceedings, 2024)
Today, modern technological developments are placing literary processes in a new dimension, where artificial intelligence actively participates, although its role is still a subject of debate. Critics often argue whether it is possible to distinguish betw